A randomized prospective open-label controlled trial comparing the performance of a connected monitoring interface versus physical routine monitoring in patients with rheumatoid arthritis. (6th October 2020) - Pers, Yves-Marie; Valsecchi, Verushka; Mura, Thibault; Aouinti, Safa; Filippi, Nathalie; Marouen, Sarah; Letaief, Hind; Le Blay, Pierre; Autuori, Michel; Fournet, Dominique; Mercier, Grégoire; Ferreira, Rosanna; et al.
Abstract: Objectives: In RA, telemedicine may allow tight control of disease activity while reducing hospital visits. We developed a smartphone application connected with a physician's interface to monitor RA patients. We aimed to assess the performance of this e-Health solution in comparison with routine practice in the management of patients with RA. Methods: A six-month pragmatic, randomized, controlled, prospective, clinical trial was conducted in RA patients with high to moderate disease activity starting a new DMARD therapy. Two groups were established: 'connected monitoring' and 'conventional monitoring'. The primary outcome was the number of physical visits between baseline and six months. Secondary outcomes included adherence, satisfaction, changes in clinical, functional and health status scores (Short-Form 12). Results: Of the 94 randomized patients, 89 completed study: 44 in the 'conventional monitoring' arm and 45 in the 'connected monitoring' arm. The total number of physical visits between required baseline and six-month visits was significantly lower in the 'connected monitoring' group [0.42 (0.58) vs 1.93 (0.55); P  <0.05]. No differences between groups were observed in the clinical and functional scores. A better quality of life for Short-Form 12 subscores (Role-Physical and Role-Emotional) were found in the 'connected monitoring' group. Conclusion: Our results suggest that connected monitoring reduces the number of physical visits while maintaining a tight control of disease activity and improving quality of life in patients with RA starting a new treatment. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT03005925.